VD_FINDINFO Décision / 2010 / 85 vom 27. Mai 2010 - VD Tribunal cantonal (2010)
RADIATION DU RÔLE, PROCÈS DEVENU SANS OBJET, TRANSACTION JUDICIAIRE | 61 let. a LPGA, 109 al. 1 LPA-VD, 2 LPA-VD, 91 LPA-VD, 93 al. 1 let. a LPA-VD, 94 al. 1 let. c LPA-VD, 99 LPA-VD